PROGRESSIVE FAILURE AFTER GASTRIC AND DUDEON RESECTION (Journal of Pharmaceutical Negative Results, 2022)
The scientific literature reviews on the origin of anemia and the development of anemia after gastric and duodenal resection, the state of advanced hyperchromic anemia, both experimental and clinical observations on the possibility of developing forms of anemia are given in this article.